Megyék, régiók és központjaik – modellek tükrében - Bajmócy, Péter; Kiss, János (Tér és Társadalom, 1999)
In this study the authors introduce the main results of some simple quantitative models in the theme of the connection of regions, counties and its centres. First they examined the connection (namely their location and population) of the county-seats (18 plus Budapest) and the other settlements. In the first two models they take into consideration just the location of the settlements. All the settlements belong to the nearest (by air in the first, and on route in the second model). Only the lack of bridges on the main rivers (etc. Danube and Tisza River) and the Lake Balaton could cause differences between the two models. The third one is a gravity model. First the authors used the classic exponent, the second power of the distance, but because of the large population (and also economical importance) of Budapest more than half of the country would be belonged to the "theoretical county of Budapest". So atter raising the exponent, the authors made an other gravity model with the fourth power of the distance. It is interesting to compare the results of these models and the administrative counties of Hungary. At more than two thirds of the settlements the theoretical "county-seats" in all the three models and the administrative one is the same. Ön the other hand more than 10 percent of the settlements gravitate to the same town in all models, but this town is not the really county-seat of these settlements. The administrative division has the largest problems at these territories, where a lot of these kind of settlements are next to each other. (the environ of Baja, Sopron, the southern part of Vas county etc.). When Hungary will join to the EU the importance of the regions (NUTS II. level) will increase, so it is interesting to examine the connection of the 7 potential regional centres and the other settlements as well. The gravity-region of Budapest is much more larger than the potential administrative unit (Middle Hungary region), but the real region-level hinterland of the capital is larger as well.